The Relationship Between Medical Staff Workload and Response Time in Catastrophic Emergency Cases at Sembiring General Hospital, Deli Tua, 2023 - Herlina (Institut Kesehatan Medistra Lubuk Pakam, 2025)
Workload is one of the critical factors that can influence the response time of medical staff in handling emergency cases, particularly catastrophic emergencies that require immediate action. This study aimed to examine the relationship between medical staff workload and response time in catastrophic emergency cases at Sembiring General Hospital, Deli Tua, in 2023. An analytical study with a cross-sectional design was applied. The sample consisted of 40 medical staff working in the Emergency Department, selected through purposive sampling. Data were collected using a workload questionnaire and response time observation sheet, then analyzed using the chi-square test.The results showed that most medical staff experienced high workloads, while their response times tended to fall within the moderate to slow categories. Statistical analysis indicated a significant relationship between workload and response time (p < 0.05). This finding confirms that higher workloads are associated with slower response times in managing emergency patients.In conclusion, optimal workload management is essential to improve medical staff responsiveness. Hospital management should focus on fair task distribution, increasing the number of staff during peak hours, and ensuring adequate supporting facilities to provide faster, more effective, and safer emergency care for patients.